Nociceptive stimulation induces expression of Arc/Arg3.1 in the spinal cord with a preference for neurons containing enkephalin - Kuhl Dietmar; Biesheuvel Karla; Jongen Joost LM; Hossaini Mehdi; Holstege Jan C (SAGE Publishing, 2010)
Abstract Background In pain processing, long term synaptic changes play an important role, especially during chronic pain. The immediate early gene Arc/Arg3.1 has been widely implicated in mediating long-term plasticity in telencephalic regions, such as the hippocampus and cortex. Accordingly, Arc/Arg3.1 knockout (KO) mice show a deficit in long-term memory consolidation. Here, we identify expression of Arc/Arg3.1 in the rat spinal cord using immunohistochemistry and in situ hybridization following pain stimuli. Results We found that Arc/Arg3.1 is not present in naïve or vehicle treated animals, and is de novo expressed in dorsal horn neurons after nociceptive stimulation. Expression of Arc/Arg3.1 was induced in an intensity dependent manner in neurons that were located in laminae I (14%) and II (85%) of the spinal dorsal horn. Intrathecal injection of brain derived neurotrophic factor (BDNF) also induced expression of Arc/Arg3.1. Furthermore, 90% of Arc/Arg3.1 expressing neurons also contained the activity marker c-Fos, which was expressed more abundantly. Preproenkephalin mRNA was found in the majority (68%) of the Arc/Arg3.1 expressing neurons, while NK-1 was found in only 19% and GAD67 mRNA in 3.6%. Finally, pain behavior in Arc/Arg3.1 KO mice was not significantly different from their wild type littermates after application of formalin or after induction of chronic inflammatory pain. Conclusions We conclude that Arc/Arg3.1 is preferentially expressed in spinal enkephalinergic neurons after nociceptive stimulation. Therefore, our data suggest that Arc/Arg3.1 dependent long term synaptic changes in spinal pain transmission are a feature of anti-nociceptive, i.e. enkephalinergic, rather than pro-nociceptive neurons.